Patient Satisfaction, Provider Productivity, and Efficacy of a Standardized Preparatory Toolkit With Broad Telemedicine Adaptation in an Outpatient Urology Clinic. Issue 9 (30th September 2022) - Overholt, Tyler L.; Dutta, Rahul; Smith, Whitney R.; Velet, Liliya P.; Xu, Raymond; Matthews, Catherine A.
Abstract : Importance: The COVID-19 pandemic prompted telemedicine adoption. In March 2020, we developed an implementation toolkit with a nursing protocol for patient preparation before tertiary care urology clinic visits. Objectives: Our primary objective was to determine patient satisfaction after implementation of a telemedicine toolkit. Our secondary objective was to assess downstream productivity generated from telehealth visits. Study Design: We prospectively conducted a postvisit survey that included the Telehealth Usability Questionnaire, a validated survey assessing patient satisfaction, for all patients with documented completion of the nursing protocol to assess patient experience and satisfaction. We then performed a retrospective chart review of all telemedicine visits to determine downstream outcomes, including imaging and procedure scheduling. Results: Between April and May 2020, 1, 422 visits were completed, of which 265 had complete nursing protocol documentation. Eighteen of 265 (6.8%) reported setup assistance. Four (1.8%) were unsuccessful and converted to a nonvisual phone visit. Overall, 186 (70.1%) completed the Telehealth Usability Questionnaire with a mean score of 118.31 ± 23.44. High satisfaction was reported regardless of race, marital status, income, education, employment status, or travel distance. Younger age ( P = 0.017) and female sex ( P = 0.017) were associated with greater satisfaction. Of 1, 422 total visits, imaging was ordered in 29%, office procedures scheduled in 14%, and surgery scheduled in 14%. New visits were more likely to result in procedure and surgery scheduling than returns ( P < 0.0001). Conclusions: Our telemedicine toolkit designed to maximize patient engagement was successful in achieving patient-provider connectivity in 98% of patients with high satisfaction. Telemedicine visits are effective to provide comprehensive urologic care with implications beyond the pandemic.